(292) التغير الهيكلي لقطاع المعلومات في مصر (بالتركيز على العمالة) The Structural Transformation of the Egyptian Information Sector with Emphasis on Labour Force - محرم الحداد; اجلال راتب; محمد عبد الشفيع عيسى; زلفى عبدالفتاح شلبي (معهد التخطيط القومى, 2019)
24سم